Using multiplex PCR as a diagnostic tool to detect methicillin resistant Staphylococcus aureus - Akgün, Sadık; Sayiner, Hakan Sezgin (Journal of Surgery and Medicine, 2018)
Aim: The goal of this report was to deliver the methicillin resistant Staphylococcus aureus (MRSA) reports to the clinician and prevent the treatment delays, investigating the efficacy in addition to diagnostic testing and contact isolation strategies for intensive care unit (ICU) patients with MRSA. Methods: In this report, 320 Staphylococcus aureus strains identified as coagulase positive were cultured from hospitalized ICU patients between 2015 and 2017. Wound swabs were performed and bacteria cultures were evaluated for identification and antibiotic susceptibility testing using a culture antibiogram. Among these cultures from the swabs, MRSA was identified and subsequently screened for the MecA gene using rapid Multiplex polymerase chain reaction (PCR). Results: MRSA was detected in 67 of 320 strains, because of oxacillin resistance was detected by working with a fully automated culture antibiogram device. In addition, MRSA positivity was detected because of the high MecA gene expression in 56 of these 67 strains using rapid multiplex PCR. Conclusion: With greater than 86% sensitivity, patients were able to get early treatment for MRSA due to the rapid screening analysis using Multiplex PCR. This method, as a diagnostic tool, may be of benefit in other diseases.